2018
DOI: 10.1186/s13690-018-0253-9
|View full text |Cite
|
Sign up to set email alerts
|

Women decision-making capacity and intimate partner violence among women in sub-Saharan Africa

Abstract: BackgroundViolence against women is a common form of human rights violation, and intimate partner violence (IPV) appears to be the most significant component of violence. The aim of this study was to examine the association between women decision-making capacity and IPV among Women in Sub-Saharan Africa. The study also looked at how socio-demographic factors also influence IPV among Women in Sub-Saharan Africa.MethodsThe study made use of pooled data from most recent Demographic and Health Survey (DHS) conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
128
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(176 citation statements)
references
References 38 publications
25
128
6
1
Order By: Relevance
“…Women who accept any form of violence by intimate partners by justifying reasons were 1.9 times more likely to have experienced violence compared to those who did not accept violence by justifying reasons. is is consistent with the findings in Nepal [35] and the Demographic and Health Survey conducted from six African countries [33]. e possible reason might be due to the socioculture of the community norms that privilege gives higher status to men and lower status to women and considered IPV as normal, and this may increase violence.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Women who accept any form of violence by intimate partners by justifying reasons were 1.9 times more likely to have experienced violence compared to those who did not accept violence by justifying reasons. is is consistent with the findings in Nepal [35] and the Demographic and Health Survey conducted from six African countries [33]. e possible reason might be due to the socioculture of the community norms that privilege gives higher status to men and lower status to women and considered IPV as normal, and this may increase violence.…”
supporting
confidence: 89%
“…is is supported by the findings from South Africa and the Demographic and Health Survey in sub-Saharan African countries [30,33]. e possible explanation could be that the married ones understand each other and are more likely to compromise on certain issues which brings less conflict in their homes.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Other adjusted variables were the age, level of education, and occupation of the responding women's spouses or partners, the household wealth and union types of the women. Previous studies [8,16,27,[34][35][36][37][38][39][40][41][42][43][44] have linked the selected explanatory variables to IPV in a variety of contexts. Operational definitions of all outcome and explanatory variables are presented in Table 2.…”
Section: Measures and Variablesmentioning
confidence: 99%
“…A multi-country study in 46 low-and-middle-income countries (LMICs) using wealth quintiles found that poorer women were more vulnerable to IPV (23). Studies on the relationship between poverty and IPV have similar ndings (16,24). The R.E.S.P.T framework aims to tackle this multifaceted problem with a multifaceted solution, aiming strategies at several risk and protective factors simultaneously.…”
Section: Introductionmentioning
confidence: 99%